MALDI Mass Spectrometry Imaging of Early‐ and Late‐Stage Serous Ovarian Cancer Tissue Reveals Stage‐Specific N‐Glycans. Issue 21 (16th August 2019) - Briggs, Matthew T.; Condina, Mark R.; Ho, Yin Ying; Everest‐Dass, Arun V.; Mittal, Parul; Kaur, Gurjeet; Oehler, Martin K.; Packer, Nicolle H.; Hoffmann, Peter
Abstract: Epithelial ovarian cancer is one of the most fatal gynecological malignancies in adult women. As studies on protein N‐ glycosylation have extensively reported aberrant patterns in the ovarian cancer tumor microenvironment, obtaining spatial information will uncover tumor‐specific N‐ glycan alterations in ovarian cancer development and progression. matrix‐assisted laser desorption/ionization (MALDI) mass spectrometry imaging (MSI) is employed to investigate N‐ glycan distribution on formalin‐fixed paraffin‐embedded ovarian cancer tissue sections from early‐ and late‐stage patients. Tumor‐specific N‐ glycans are identified and structurally characterized by porous graphitized carbon‐liquid chromatography‐electrospray ionization‐tandem mass spectrometry (PGC‐LC‐ESI‐MS/MS), and then assigned to high‐resolution images obtained from MALDI‐MSI. Spatial distribution of 14 N‐ glycans is obtained by MALDI‐MSI and 42 N‐ glycans (including structural and compositional isomers) identified and structurally characterized by LC‐MS. The spatial distribution of oligomannose, complex neutral, bisecting, and sialylated N‐ glycan families are localized to the tumor regions of late‐stage ovarian cancer patients relative to early‐stage patients. Potential N‐ glycan diagnostic markers that emerge include the oligomannose structure, (Hex)6 + (Man)3 (GlcNAc)2, and the complex neutral structure, (Hex)2 (HexNAc)2 (Deoxyhexose)1 + (Man)3 (GlcNAc)2 . The distribution of these markers is evaluated using a tissue microarray of early‐ and late‐stage patients.